Clinical features and treatment of patients with esophageal cancer and a history of gastrectomy: a multicenter, questionnaire survey in Kyushu, Japan. Issue 8 (6th November 2015) - Okumura, H.; Mori, N.; Tanaka, T.; Morita, M.; Toh, Y.; Saeki, H.; Maehara, Y.; Nakamura, K.; Honda, H.; Yoshida, N.; Baba, H.; Natsugoe, S.
Summary: It is still controversial whether patients with a history of gastrectomy have high risk of esophageal carcinogenesis. On the other hand, the treatment strategy for esophageal cancer patients after gastrectomy is complicated. The association between histories of gastrectomy and esophageal carcinogenesis was retrospectively analyzed, and the treatment of esophageal cancer patients after gastrectomy was evaluated based on questionnaire data collected from multiple centers in Kyushu, Japan. The initial subject population comprised 205 esophageal cancer patients after gastrectomy. Among them, 108 patients underwent curative surgical treatment, and 70 patients underwent chemoradiation therapy (CRT). The time between gastrectomy and esophageal cancer development was longer in peptic ulcer patients (28.3 years) than in gastric cancer patients (9.6 years). There were no differences in the location of esophageal cancer according to the gastrectomy reconstruction method. There were no significant differences in the clinical background characteristics between patients with and without a history of gastrectomy. Among the 108 patients in the surgery group, the 5‐year overall survival rates for stages I ( n = 30), II ( n = 18), and III ( n = 60) were 68.2%, 62.9%, and 32.1%, respectively. In the CRT group, the 5‐year overall survival rate of stage I ( n = 29) was 82.6%, but there were no 5‐year survivors in other stages. The 5‐year overall survival rate of patients with CR ( n = 33) or salvage surgery ( n = 10) was 61.2% or 36%, respectively. For the treatment of gastrectomized esophageal cancer patients, surgery or CRT is recommended for stage I, and surgery with or without adjuvant therapy is the main central treatment in advanced stages, with surgery for stage II, neoadjuvant therapy + surgery for stage III, and CRT + salvage surgery for any stage, if the patient's condition permits.